Identifying medications with similar packages in a Brazilian hospital: a multiple step approach - Letícia L. MACIEL; Maria D. SILVA; Mariana G. NASCIMENTO; Adriano M. REIS; Renata R. MENEZES; Aline L. ANDRADE; Cássia L. FERREIRA; Cristiane P. REZENDE; Gisele C. GOULART (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2021)
Objective: To describe the identification of drugs with similar primary packaging available in a large teaching hospital. Methods: This is a descriptive study carried out using a multi-step approach. First, the small volume parenteral drugs and oral solutions available at the institution (Step I) were listed. Then, from the list developed in Step I, groups of drugs with similar packaging (double, trio or foursome) were identified according to their characteristics (Step II). These groups were then visually evaluated by the pharmacy team (Step III), and later by the internal community of the institution (Step IV). Results: A total of 233 drugs in the pharmaceutical forms of interest were available at the institution (Stage I). In step II, 62 groups with similar primary packaging were identified. After evaluation by the pharmacy team, 19 groups remained (Stage III), which were then evaluated by the internal community, generating a final list of 15 groups of drugs with similar primary packaging. Among these, the pharmaceutical form of  parenteral use (80%) and the amber ampoule as primary packaging (46.7%) were frequent. Conclusion: The results of the study point to the applicability and adequacy of the multistep approach to identify the presence of groups of drugs with similar primary packaging in a real-world scenario. The identification of these groups of drugs in health care institutions is the first important step to plan strategies to minimize errors involving similar packaging, thus increasing the safety of medication use in the hospital environment.